Emerging India security and foreign policy perspectives - Sisodia, N. S.; Uday Bhaskar, C. (Chitrapu) 1951- (Institute for Defence Studies and Analyses and Promilla & Co., Publishers in association with Bibliophile South Asia, 2005)
Contributed articles on foreign relations of India post 1984 and national security concerns presented earlier at a seminar celebrating 40th anniversary of Institute for Defence Studies and Analyses.